Calcium-induced skim milk gels: Effect of milk powder concentration and pH on tribo-rheological characteristics and gel physico-chemical properties - Olivares, María Laura (2021)
The physico-chemical and tribo-rheological characteristics of calcium-induced skim milk gels obtained by heating of milk dispersions prepared with different concentrations of skim milk powder (10, 20 and 30% w/w) and calcium chloride (30, 60 and 90 mmol kg−1) were studied. The effect of pH on the gelation and on the final gel structure was also analyzed. For this purpose, the pH of selected samples was readjusted to the natural pH of milk of 6.66 after the calcium salt addition. The gelation process was analyzed by rheometry throughout temperature and time sweeps. Gelation at temperatures lower than 70 °C was observed in samples with 10% w/w of skim milk powder (SM) and 30 mmol kg−1 of calcium chloride or similar ratio, when the amount of calcium remaining in the serum phase is enough to induce gel formation. The results obtained from temperature sweeps also suggest that the pH strongly affects the temperature at which gelation initiates. Structuring parameters confirmed these results. From time sweeps, it was observed that the kinetics of gelation depended on both composition and pH. Gels obtained using higher SM concentrations (20 and 30% w/w) showed better physical properties (low syneresis and high water holding capacity). Confocal laser microscopy images also showed a more homogeneous structure in those samples. Higher SM and calcium chloride concentrations improved the lubrication characteristics analyzed by tribology. Friction factors at 10 mm s−1 (typical speed in oral processing) decreased as the SM concentration increased. It is concluded that calcium-induced skim milk gels with different microstructure can be obtained by varying the concentration of skim milk powder and calcium salt added, and pH adjustment.